ANALISIS PENINGKATAN PEMBELAJARAN AL-QUR’AN SISWA SD PLUS TADIKA RAYA SUMATRA UTARA - Arpin Aminuddin Hrp; Nasrulloh; Rizka Qurrota Ayuni; Khuntum Khaira Ummah; Hamidatul Latifah (Fakultas Tarbiyah Institut Ilmu Al-Qur'an (IIQ) Jakarta, Indonesia, 2023)
Al-Qur'an learning is increasing very rapidly, especially in various Islamic educational institutions where students already have good skills in reading the Al Qur'an, In fact, quite a lot of them are able to memorize Al-Qur'an and complete it This research aims to analyze the improvement in Al-Qur'an learning for elementary school students plus Tadika Raya. This research uses a qualitative approach with descriptive methods. Data collection techniques use interviews and documents. The object of this research comes from students at Elementary School Plus Tadika Raya North Padang Lawas, North Sumatera. The results of this research indicate that the increase in Al-Qur'an learning of students at Elementary School Plus Tadika Raya is proven by three factors, namely Al-Qur'an learning activities, teaching materials, and social activities. Learning activities include learning iqra', tahsin recitations, memorizing deposits and mutabaah books, tajwid science, Qur'an tartil competition, and tahfidz graduation category juz part 29 and 30 eaching materials include books on iqra', tsaqifah and the science of tajwid written by K.H Imam Zarkasyi. The social environment includes teachers, parents and friends.